Examination of patients with different forms RFL MMOC - Sobirov Sh.S (Research Parks Publishers, 2021)
Lichen planus (LP) is one of the most common, often recurrent and therapy-resistant dermatoses localized to the oral mucosa. The incidence of the disease varies from 30 to 35% among the entire pathology of the oral mucosa (OOM), affecting mainly women of the climacteric period and menopause [Kubanova A. A. 2010, Perlamutrov Yu.N. 2010, Julia S. Lehman 2009]. Psychoemotional stress is considered to be one of the triggering factors in the onset of LPO OCPR, and the activity of the processes of free radical oxidation of lipids and the lack of capacity of the antioxidant potential of the body determine the ineffectiveness of therapy, as a result of which it can be concluded that it is necessary to include drugs with antioxidant and anxiolytic properties in the traditional treatment regimen